Brief Report From the 3rd International Meeting on Bone Marrow Adiposity (BMA 2017) - Corsi, Alessandro; Palmisano, Biagio; Tratwal, Josefine; Riminucci, Mara; Naveiras, Olaia (Frontiers in Endocrinology, 2019)
The 3rd International Meeting on Bone Marrow Adiposity (BMA) was held at the Olympic Museum in Lausanne, Switzerland, on August 31st and September 1st, 2017. This brief monograph summarizes the scientific contents of the meeting and highlights the birth of the International Bone Marrow Adiposity Society (BMAS).